An analytical perspective on the Fellowship Narrative of Genesis 18:1–15 - Keun, Ahn Sang (HTS teologiese studies, 2010)
The narrative in Genesis 18:1–15 deals with God’s visit to Abraham at Mamre. The general tendency in the interpretation of this narrative is to focus on Abraham’s hospitality. It is usually interpreted as an example of his righteousness, in line with Hebrews 13:2, or with the test motive of the Greek myth of the birth of Orion. These interpretations, however, seem to be in conflict with the narrator’s own theological views.This study, therefore, attempts to explore the view point of the author of the Fellowship Narrative (Gn 18:1–15) within the context of the larger Abraham narrative (Gn 11:27–25:11). The method used for the investigation is mainly that of narrative criticism. Attention is paid to the narrator’s various literary skills: ‘linking structure with preceding episode’ (Gn 18:1a), the ‘sandwiched structure’ of the larger context (Gn 18:1–21:7), the unique plot sequence, as well as repeated clue words and phrases (such as ‘laugh’, ‘Sarah’ and ‘this time next year’). These literary aspects are used by the narrator to depict the faithfulness of the Lord who fulfils what he promised. The conclusion of this study overturns the traditional interpretations of the Fellowship Narrative.